Discretized hexagonal boron nitride quantum emitters and their chemical interconversion. (12th March 2023) - Kozawa, Daichi; Li, Sylvia Xin; Ichihara, Takeo; Rajan, Ananth Govind; Gong, Xun; He, Guangwei; Koman, Volodymyr B; Zeng, Yuwen; Kuehne, Matthias; Silmore, Kevin S; Parviz, Dorsa; Liu, Pingwei; et al.
Abstract: Quantum emitters in two-dimensional hexagonal boron nitride (hBN) are of significant interest because of their unique photophysical properties, such as single-photon emission at room temperature, and promising applications in quantum computing and communications. The photoemission from hBN defects covers a wide range of emission energies but identifying and modulating the properties of specific emitters remain challenging due to uncontrolled formation of hBN defects. In this study, more than 2000 spectra are collected consisting of single, isolated zero-phonon lines (ZPLs) between 1.59 and 2.25 eV from diverse sample types. Most of ZPLs are organized into seven discretized emission energies. All emitters exhibit a range of lifetimes from 1 to 6 ns, and phonon sidebands offset by the dominant lattice phonon in hBN near 1370 cm −1 . Two chemical processing schemes are developed based on water and boric acid etching that generate or preferentially interconvert specific emitters, respectively. The identification and chemical interconversion of these discretized emitters should significantly advance the understanding of solid-state chemistry and photophysics of hBN quantum emission.